The influence of synthesis of the initial mixture and blowing agents on the formation of a porous structure - Чейлытко, Андрей Александрович (Eastern-European Journal of Enterprise Technologies, 2015)
It is shown that a porous structure affects the thermophysical characteristics of the material. The analysis of experimental studies on the influence of synthesis of the initial mixture on the formation of a porous structure was performed. Blowing agents in swelling or foaming of the mixture are gases released in the chemical reaction (oxygen, water vapor, hydrogen, carbon dioxide, etc.). The paper presents the reactions with the greatest decline in the Gibbs free energy, i.e. most likely to occur. Based on the analysis, the principal blowing agents were identified, and also the dependencies of material properties on the synthesis of the initial components were found. The absence (at the present stage of scientific discovery) of the possibility of quality control of porous structure by synthesis of the initial mixture was shown. Integrated indicators of the porous structure (porosity, number of pores, position of pores in space, the shape of the pores, pore formation energy), which will allow to develop a new control methodology of the porous structure were proposed.